Prevalence of Newcastle disease in chickens in Ethiopia: a systematic review and meta-analysis - Tibebu, A.; Bahiru, A.; Yitbarek, T.; Assefa, Ayalew (Informa UK Limited, 2024)
Newcastle disease (ND) severely affects domestic chickens and birds like ducks, turkeys, and pigeons. This review, based on 31 studies in Ethiopia from 2000-2024, analyzed ND prevalence using a random-effects model. Results show 83.3% of studies came from Oromia and Amhara regions. The overall ND prevalence was 22%, with the highest rates in the South (45%) and lowest in Oromia (17%). Serological tests showed higher prevalence (28%) than molecular tests (18%). Males and domestic chickens had lower odds than females and exotics. The review indicated four NDV genotypes (I, II, VI, VII) circulating in Oromia and three (II, VI, VII) in Amhara. Publication bias appeared in funnel plot, but did not significantly impact the overall results. The high ND prevalence and study variations underscore the urgent need for further research and prevention.